Anatomi berorientasi klinis : Edisi kelima, Jilid 3 / Keith L. Moore dan Arthur F. Dalley; Penerjemah, Huriawati Hartanto - MOORE, Keith L.; DALLEY, Arthur F.; HURIAWATI Hartanto (Erlangga, 2013)
xix, 280 hlm. : ilus. ; 28,5 cm. + CD